Do Habitat Corridors Provide Connectivity? - Paul Beier; Reed F. Noss (Conservation Biology, 1998)
Skeptics have questioned the empirical evidence that corridors provide landscape connectivity. Some also have suggested dangers of corridors. We reviewed published studies that empirically addressed whether corridors enhance or diminish the population viability of species in habitat patches connected by corridors. A randomized and replicated experimental design has not been used—and we argue is not required—to make inferences about the conservation value of corridors. Rather, studies can use observational or experimental analyses of parameters of target populations or movements of individual animals. Two of these approaches hold the greatest promise for progress, especially if the shortcomings of previous studies are remedied. First, experiments using demographic parameters as dependent variables—even if unreplicated—can demonstrate the demographic effects of particular corridors in particular landscapes. Such studies should measure demographic traits before and after treatment in both the treated area (corridor created or destroyed) and an untreated area (habitat patches isolated from one another). This approach is superior to observing the demographic conditions in various landscapes because of the tendency for corridor presence to be correlated with other variables, such as patch size, that can confound the analysis. Second, observations of movements by naturally dispersing animals in fragmented landscapes can demonstrate the conservation value of corridors more convincingly than can controlled experiments on animal movement. Such field observations relate directly to the type of animals (e.g., dispersing juveniles of target species) and the real landscapes that are the subject of decisions about corridor preservation. Future observational studies of animal movements should attempt to detect extra‐corridor movements and focus on fragmentation‐sensitive species for which corridors are likely to be proposed. Fewer than half of the 32 studies we reviewed provided persuasive data regarding the utility of corridors; other studies were inconclusive, largely due to design flaws. The evidence from well‐designed studies suggests that corridors are valuable conservation tools. Those who would destroy the last remnants of natural connectivity should bear the burden of proving that corridor destruction will not harm target populations. Proveen Conectividad los Corredores de Hábitat? Algunos escépticos han cuestionado la evidencia empírica de que los corredores proveen conectividad al paisaje. Otros han sugerido los peligros de los corredores. Revisamos estudios publicados que abordaron empíricamente si los corredores fomentan o disminuyen la viabilidad de poblaciones de especies en parches de hábitat conectados por corredores. A la fecha no se ha llevado a cabo un diseño experimental randomizado y con réplicas para realizar inferencias sobre el valor de los corresdores en la conservación—y nosotros argüímos que no es necesario. En cambio, los estudios pueden emplear análisis observacional o experimental de parámetros de poblaciones de interés o movimientos individuales de animales. Dos de estas aproximaciones son muy prometedoras y pueden progresar, especialmente si las limitantes de los estudios previos son remediadas. Primero, los experimentos que usan parámetros demográficos como variables dependientes—aún si no son replicados—pueden demostrar efectos demográficos de corredores en paisajes particulares. Estos estudios deberán medir características demográficas antes y después del tratamiento, tanto en el área tratada (corredor creado o destruído) como en un área no tratada (parches de hábitat aislados unos de otros). Esta aproximación es superior a observar las condiciones demográficas en varios paisajes puesto que la presencia de un corredor tiende a estar correlacionada con otras variables, como lo es el tamaño del parche lo que puede confundir el análisis. Segundo, las observaciones de movimientos de animales que se desplazan normalmente en paisajes fragmentados puede demostrar el valor de los corredores en la conservación de manera mas convincente que los experimentos controlados sobre animales en movimiento. Este tipo de observaciones de campo están directamente relacionades con el tipo de animal (e.g., juveniles de la especie de interés dispersándose) y con el tipo de paisajes que están sujetos a las decisiones de preservación de corredores. Los estudios observacionales de movimientos de animales a futuro deberán tratar de detectar movimientos extra‐corredores y enfocarse a especies sensitivas a la fragmentación y para las cuales los corredores son factibles a ser propuestos. Menos de la mitad de los 32 estudios revisados provee datos persuasivos referentes a la utilidad de los corredores; otros estudios fueron inconclusos, mayormente debido a diseños defectuosos. Las evidencias de estudios bien diseñados sugieren que los corredores son herramientas valiosas de conservación. Aquellos que intentan destruir los últimos remanentes de conectividad natural deberían sustentarse demostrando que la destrucción de los corredores no afectará a poblaciones de interés.